The Effect Of Net Profit And Operating Cash Flows On Dividend Policy On Manufacturing Companies Listed On The Indonesia Stock Exchange - Desy Marito Panjaitan (JURNAL ILMIAH SOCIO SECRETUM, 2023)
This study aims to examine the effect of net income and operating cash flow on dividend policy in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The data method is carried out by using the library research method (Library Research) and the field research method (Field Research) where the data used by the researcher is the financial statements of each sample published through www.idx.co.id. The study population was 50 companies with purposive sampling technique obtained 10 companies that became the research sample so that the total obtained was 30 data. The analysis technique used is multiple linear regression analysis using the SPSS version 22 program. Then the research trial using the t test and the F test. The results of the research partially show that the Net Profit variable has a significant effect on Dividend Policy (DPR) where the tcount is -2.520 <ttable 1.703, and the Operating Cash Flow variable has no effect on Dividend Policy (DPR) where the tcount is -1.239 <ttable 1.703. The results of the research simultaneously prove that Net Profit and Operating Cash Flow have a significant effect on Dividend Policy (DPR) in Manufacturing Companies in the Consumer Goods Sector in the Indonesia Stock Exchange where the value of Fcount 3.547> Ftable 3.35. The coefficient of determination (R2) shows a numerical value of 20.8% and the remaining 79.2%. By other variables that are not accurate in this study.